2016
DOI: 10.1080/01441647.2016.1217283
|View full text |Cite
|
Sign up to set email alerts
|

A review of guidelines for including wider economic impacts in transport appraisal

Abstract: In this paper we examine how 23 industrialized countries treat wider economic impacts in transport appraisals. We identify 12 different types of impacts based on these countries' appraisal guidelines. Agglomeration impacts and Production changes in imperfect markets are the most widely accepted, being recognized by 14 and 10 countries, respectively. However, about half of the impacts are mentioned by only one country, and few recommend including the impacts directly in cost-benefit analyses. Several countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…al. [42] investigated how 22 developed countries (Nordic countries, 15 countries in the EU, the USA, Canada, Switzerland, Australia, New Zealand, and Japan) treat WEBs in transport project appraisals. They found that 15 countries recognized at least one category of WEB, and only 10 of them recommended methods for their assessment.…”
Section: Transport Infrastructure Investment and Economymentioning
confidence: 99%
“…al. [42] investigated how 22 developed countries (Nordic countries, 15 countries in the EU, the USA, Canada, Switzerland, Australia, New Zealand, and Japan) treat WEBs in transport project appraisals. They found that 15 countries recognized at least one category of WEB, and only 10 of them recommended methods for their assessment.…”
Section: Transport Infrastructure Investment and Economymentioning
confidence: 99%
“…After examining how 23 industrialized countries treat WEIs in transport appraisals, Wangsness et al [2] concluded that even though the concept of WEIs has matured over the last decade, there is still relatively little consensus on the magnitude and relevance of WEIs, and further research is needed to better understand the nature of WEIs. Our paper aims to offer some insights into the area from a developing country's perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers argue that large transport projects, together with the appropriate policies, can generate additional benefits over the user benefits calculated in the traditional Cost-Benefit Analysis (CBA) method. The assessment of WEIs has been included in the guidelines for transport appraisal in many countries, e.g., the U.K., the Netherlands, and so on [1,2]. Nowadays, major cities in developing countries are undergoing massive transportation infrastructure construction, which has significant impacts on the land use and economic activities in these cities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The operation of CGE models also tends to be a 'black box' where model mechanics are hidden or difficult to understand. Thus far, only the Netherlands has guidelines detailing the use of CGE models in WEI appraisal (Wangsness et al, 2016).…”
mentioning
confidence: 99%